Decreasing the Saturated Contact Angle in Electrowetting‐on‐Dielectrics by Controlling the Charge Trapping at Liquid–Solid Interfaces. (3rd March 2016) - Li, Xiangming; Tian, Hongmiao; Shao, Jinyou; Ding, Yucheng; Chen, Xiaoliang; Wang, Li; Lu, Bingheng
Abstract : Contact angle saturation in electrowetting‐on‐dielectrics (EWOD) has restricted the tuning range of the wettability of a solid surface, which has generally limited the performances of EWOD devices such as digital microfluidics, lab‐on‐chip, electronic displays, and so forth. Here, a method is proposed for decreasing the saturated contact angle by controlling the behavior of charge trapping at the liquid–solid interface. An unexpected phenomenon is uncovered: for a short time the contact angle reaches smaller values before it retreats to its saturation value, which is caused by charge trapping at the liquid–solid interface. Experimental results suggest that the trapped charges can be repeatedly detrapped and retrapped when the polarity of the applied voltage is periodically reversed, which results in contact angles retreating periodically. By applying a well‐modulated voltage signal with reversing polarity, the retreat movement of the contact angle can be controlled to obtain a value significantly smaller than the previously possible threshold. As a specific application of this method, an economic two‐step process which is developed potentially suitable for mass‐producing large‐area flexible microlens arrays with controllable curvatures and wide fields of view. Abstract : An approach to overcome the classical contact angle limit in electrowetting‐on‐dielectrics is presented, allowing impromvement of a variety of applications. The newly proposed method decreases the saturated contact angle by using a square‐wave voltage with time‐modulated polarities to control the charge trapping at the liquid‐solid interfaces. This method works well with various materials and has been used for forming large‐area microlens arrays.